Gideon Falls. 1, The black barn - Lemire, Jeff; Sorrentino, Andrea (Portland, OR : Image Comics, Inc., 2018)
A reclusive young man and a washed-up priest become obsessed with the legend of the "black barn," a spectral building that appears throughout history leaving death and madness in its wake.
"Contains material originally published in single magazine form as Gideon Falls #1-6."
Chiefly illustrations.
Keywords: Comic books, strips, etc; Comic books, strips, etc